2016
DOI: 10.1089/aivt.2015.0028
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of NephrotoxicityIn VitroUsing a Transparent Conducting Polymer Device

Abstract: Electrical methods for monitoring cell toxicity are becoming increasingly popular because of their amenability for longer-term, continuous, and label-free monitoring. Microfabrication techniques are also opening the way for miniaturization of devices and integration with microphysiometer or lab-on-chip-type devices. In the present work, we demonstrate the use of a transparent conducting polymer device, termed the ''organic electrochemical transistor'' (OECT), which we have used to monitor the effects of a subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…OECTs have been used to monitor not only the integrity of highly resistant barrier‐type tissue layers, but also the coverage of adherent but leaky, nonbarrier cell layers . In the OECT, holes in the channel between the source and drain electrodes are depleted by cations pushed from the electrolyte into the channel due to a bias at a gate electrode ( V G ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OECTs have been used to monitor not only the integrity of highly resistant barrier‐type tissue layers, but also the coverage of adherent but leaky, nonbarrier cell layers . In the OECT, holes in the channel between the source and drain electrodes are depleted by cations pushed from the electrolyte into the channel due to a bias at a gate electrode ( V G ).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of different OECT channel geometries were used, including 10 × 10 μm, 10 × 100 μm, and 50 × 50 μm. Previous studies have shown that data can be compared between transistors of different channel geometry …”
Section: Methodsmentioning
confidence: 99%
“…OECTs have been shown to monitor cell coverage 107 as well as barrier tissue formation and health. [108][109][110][111][112] The majority of these measurements involve the growth of a cell monolayer between the channel and the gate, which introduces an extra barrier for ion motion in the electrolyte and alters the characteristics of the OECT. 113 The same principle was applied to study ion channels in supported lipid bilayers assembled on PEDOT:PSS channels.…”
Section: Applications Bioelectronicsmentioning
confidence: 99%
“…[ 185 ] Of note are poly (3,4‐ethlyenedioxythiophene) doped (p‐type) with poly (styrene sulfonate) (PEDOT:PSS)‐based electrodes or organic electrochemical transistors (OECTs). The detailed physical theory of OECT operation is explored elsewhere, [ 186,187 ] but such technology has been integrated into a variety of biological formats, including Transwell ALI culture, [ 178 ] planar and microfluidic devices, [ 188–191 ] PEDOT:PSS bio‐scaffolds, [ 192,193 ] self‐rolling sensors, [ 194 ] and neuromorphic devices. [ 195 ] In vivo examples include bioresorbable patches [ 196,197 ] and implantable electrocorticography devices for monitoring neuronal epileptiform discharge.…”
Section: Future Directionsmentioning
confidence: 99%